(untitled) (The Review of Diabetic Studies, 2025)
This comparative analysis explores the issues surrounding healthcare issues relating to diabetes in terms of diagnosis, treatment and prevention in the United Kingdom and Saudi Arabia. It highlights common issues such as central government education policies, inequity of diagnosis and treatment, and uses of digital technology to improve patient outcomes, while contrasting the UK’s publicly funded NHS with Saudi Arabia’s privatization efforts under the health strategy as part of the country’s Vision 2030. Findings reveal that both countries have strengths that can inform global best practices. Saudi Arabia’s use of digital health platforms and return on investment-driven prevention planning offers valuable insights for resource allocation to reduce inequities across the system. The UK’s emphasis on data-driven interventions, community engagement, and culturally competent care provides a model for inclusive and effective service delivery.